Liquid chromatography-mass spectrometry and xCELLigence real time cell analyzer revealed anticancer and antioxidant metabolites in Trianthema portulacastrum L. (Aizoaceae) - Muhali Olaide Jimoh; Mahboob Adekilekun Jimoh; Nasifu Kerebba; Olalekan Olanrewaju Bakare; Comfort Titilayomi Senjobi; Sefiu Adekilekun Saheed; Rose Kadye; Earl Prinsloo; Charles Petrus Laubscher (Elsevier, 2024)
Background: The rising incidence of cancer is a major concern globally being a leading cause of early mortality in most countries. This burden is projected to increase to 28.4 million cases worldwide by 2040 and yet, may be worsened by continuous exposure to risk factors due to a sheer shift from consumption of natural nutrients. To reverse this trend, it is imperative to source novel anticancer metabolites from plants that could minimize carcinogenic effects by suppressing the proliferation and survival of cancer cells. Purpose: This study aimed at characterizing and quantifying index anticancer and antioxidant metabolites, in the cultivars of T. portulacastrum. Methods: The Ultra-High Performance Liquid Chromatography Mass Spectroscopy (UHP-LCMS) was used to quantify and characterize index anticancer and antioxidant metabolites in shoot, root and whole plant extracts of Trianthema portulacastrum (T01,T02,T03,T04,T05,T06). The biological activity of the tested samples was monitored on the xCELLigence Real Time Cell Analyzer to determine the cytotoxicity of the extracts as a function of cell index at a specific time post dose using the concentration range of 0.16-2.5 %. Results: Based on the responses observed 48 h post exposure, all extracts showed high levels of cytotoxicity as determined by the xCELLigence apart from the root extracts. Rapid decreases in cell index (CI) values observed at higher extract percentages are highly indicative of cell death. These biological activities may be attributed to different anticancer metabolites such as epigallocatechin, glucaric acids, byakangelicin, xanthotoxin, apaensin, acetoxy-6-gingerol among other compounds of significant therapeutic benefits that were quantified with UHP-LCMS. Conclusion: These findings suggest that T. portulacastrum contains diverse anticancer metabolites which could be leveraged to develop plant-based anticancer drugs or novel chemicals with extended therapeutic utility.